Aspects of Micro Business Market Development Using the Friedman Test and Categorical Test Approaches - Artaya, I Putu; Arimbawa, I Gede; Baktiono, R Agus (Jurnal Ilmu Manajemen Advantage, 2024)
The problem faced by the research team is how to properly process market expansion for micro businesses. The research location is in Sidoarjo Regency, East Java. In the six sub-districts, there are many micro business actors who have the potential to develop but are constrained in mastering important aspects that interact with the governance and management processes of their businesses. The research sample was 69 businesses engaged in the food, beverage, and health sectors. The data testing methods used were the Friedman test and the Categorical test. The Friedman test aims to find the level of relevance and needs of the aspects used as study materials, then the Categorical test to determine the map of the aspects used as study areas, so that problem points can be seen on the quadrant map in a focused manner. The research method uses a home visit model. The purpose of this study is to help home business actors improve their product management management, so that they can attract buyers. The findings of this study are known to have five main aspects that hinder the development of 69 micro businesses in market expansion, i.e. improving packaging, utilizing technology, expedition networks, sales networks, and using brands.